Pembelajaran Qs. An – Naas dengan Metode Drill di SDN 1 Slaharwotan Ngimbang Lamongan - Romelah Romelah; Latifatul Azizah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The learning of the Qur'an and Hadith plays an important role in shaping the character and morals of the younger generation, especially at the Elementary School level. The learning of the Qur'an and Hadith is expected to instill values of faith, diversity, as well as foster attitudes of tolerance and social concern among students. This study aims to describe the learning of Surah An-Nas using the drill method, the steps of its implementation, and its execution at SDN 1 Slaharwotan Ngimbang Lamongan. This research uses a qualitative approach with a case study design, involving Islamic Education teachers and students as research subjects. Data were collected through observation, interviews, and documentation. The results of the study show that learning through the drill method is effective in improving students' ability to read and memorize the Qur'an, especially Surah An-Nas, with correct pronunciation (tartil) and fluency. The learning model is technology-based or a multimedia learning model, where teaching takes place using tools and media such as LCD projectors, active speakers, notebooks, and interactive learning CDs, demonstrating the application of technology to support the teaching and learning process, as well as increasing interactivity and effectiveness. The learning method uses repetition (drill), so it is hoped that the material being taught will be retained in students' memory. This study provides insights into the importance of teacher competence in developing teaching materials that suit the developmental needs of students, as well as the importance of adjusting teaching methods to the curriculum and the characteristics of children in Elementary Schools.